WAYS OF USING THE ARDUINO PLATFORM FOR EDUCATION OF FIRST-YEAR STUDENTS OF THE RIGA TECHNICAL UNIVERSITY - Zavjalova, Oksana; Ziborova, Viktorija; Kataļņikova, Sabina; Prokofyeva, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This paper describes the actual problem of organizing the process of professional education of students in applied problems in their specialty. The problem is considered from two aspects: pedagogical (substantive) and technical, while the solution of learning problems is planned to be realized with the help of new information technologies. The article describes two study schemes based on two programming technologies: VBA and the Arduino platform, explores the advantages and disadvantages of each scheme, and provides examples of specific tasks and the results of a survey of first-year students, which study scheme is most suitable for professional education. The study involved first-year students of RTUFaculty of Electrical and Environmental Engineering, studying the educational course “Computer science”.